Kalimat Kondisional dalam Bahasa Arab dan Bahasa Inggris: Analisis Kontrastif Bentuk dan Fungsi - Bahraen, Muhammad Jauzil; Yusuf, Muhammad (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2021)
Conditional sentences are part of the syntactic system that exists in Arabic and English. In general, the provisions relating to conditional sentences in the two languages ​​have similarities and differences. This study seeks to identify more deeply related to this matter by way of contrasting it. The subject matter relates to the similarities and differences in the form and function of conditional sentences in Arabic and English. This study is a literary style that optimizes related literature to discuss the object of research. This study formulates that the similarity in the form and function of conditional sentences in Arabic and English, namely: it can be stated implicitly, has two-sentence forms, has clear rules, has the same primary components, can be used to convey open and conjectural conditions. The differences are: Arabic markers are more varied, the characteristics of conditional sentences in Arabic focus on the markers while in English it is more on tenses, the construction of conditional sentences in Arabic is more varied than in English.